A molecular sieve / carbon nitride composite material and its preparation method and use

By preparing molecular sieve/carbon nitride composite materials, the mixing and crystallization of silicon source and aluminum source solution and carbon nitride solids are solved, the load and distribution of carbon nitride on the molecular sieve is achieved, and the high specific surface area and strong adsorption capacity of the composite material are improved, and the efficiency of photocatalytic reaction is improved.

CN116459862BActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210031324.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-12
Publication Date
2025-03-11
Estimated Expiration
2042-01-12

AI Technical Summary

Technical Problem

The prior art is difficult to achieve large loading and equal distribution of carbon nitride on the molecular sieve, resulting in a small specific surface area of ​​the composite material, which is not conducive to the full utilization of reaction sites.

Method used

By mixing the silicon source solution and the aluminum source solution, adding carbon nitride solids to form a crystallization precursor solution, and performing crystallization treatment and post-treatment steps, a molecular sieve/carbon nitride composite material is prepared.

Benefits of technology

The close combination of molecular sieve and carbon nitride is achieved, the specific surface area and adsorption capacity of the composite material are improved, and the efficiency of photocatalytic reaction is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116459862B_ABST
    Figure CN116459862B_ABST
Patent Text Reader

Abstract

The present invention relates to a novel molecular sieve / carbon nitride composite material, a preparation method thereof and its use for photocatalysis. Based on the total weight of the composite material, the molecular sieve / carbon nitride composite material comprises 25 to 70 weight % of a molecular sieve structure combined with carbon nitride. The preparation method comprises the following steps: (1) preparing a silicon-aluminum source mixed solution; (2) adding carbon nitride solid to the silicon-aluminum source mixed solution to obtain a crystallization precursor solution; (3) filling the crystallization precursor solution into a crystallization kettle for crystallization treatment; and (4) a post-treatment step. The present invention also relates to the use of the composite material for reducing carbon dioxide to CO through photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photochemical materials, and in particular to a molecular sieve / carbon nitride composite material, a preparation method thereof and a use thereof. Background Art

[0002] Carbon nitride is a new type of carbon material. It has long attracted widespread attention due to its advantages such as low density, good chemical inertness and biocompatibility. Among them, graphite carbon nitride (g-C3N4) is a polymer semiconductor material with a unique two-dimensional structure (band gap of about 2.7eV): it can be regarded as a graphite-like layered material substituted with nitrogen atoms. Each triazine ring or heptazine ring in the layer is connected by the terminal N atom to form an infinitely extended planar structure, and the layers are bonded by weak van der Waals forces. g-C3N4 is stable in nature and low in cost. As a polymer semiconductor, it also has the advantages of flexible control of chemical composition and band structure. It is a material with great potential in the field of photocatalysis.

[0003] At present, combining graphitic carbon nitride with nanomaterials to prepare porous composite materials is an important means to improve their photocatalytic performance. Molecular sieves are a type of aluminosilicate nanomaterials with a three-dimensional skeleton structure and regular pores, which have many properties that can be developed and utilized, such as ion exchange, adsorption, shape selection, catalysis, and as an assembly subject in assembled materials.

[0004] The existing technology mostly uses physical mixing methods such as mechanical grinding to load carbon nitride on molecular sieves. However, this method cannot achieve a large amount of carbon nitride on the molecular sieve and evenly distribute it. The combination of the two is unstable and easily re-forms free carbon nitride. In addition, the obtained graphite-type carbon nitride composite material has a small specific surface area, which is not conducive to the full utilization of its reaction sites, and to a certain extent limits its application.

[0005] Therefore, there is an urgent need in the art for a novel method for preparing molecular sieve / carbon nitride composite materials. Summary of the invention

[0006] A technical problem to be solved by the present invention is to provide a molecular sieve / carbon nitride composite material, wherein the composite material comprises 25-70 wt % of molecular sieve combined with carbon nitride, preferably 30%-60 wt % based on the total weight of the composite material.

[0007] According to one embodiment of the present application, the relative crystallinity of the molecular sieve / carbon nitride composite material is 25 to 70%, preferably 30-60%.

[0008] According to one embodiment of the present application, the BET specific surface area of ​​the molecular sieve / carbon nitride composite material is 100-200 m 2 / g, preferably 110-190m2 / g.

[0009] According to one embodiment of the present application, the silicon-aluminum ratio of the molecular sieve / carbon nitride composite material is 10-400, preferably 30-300.

[0010] According to one embodiment of the present application, the carbon nitride is a high specific surface area carbon nitride; under TEM observation, the high specific surface area carbon nitride has a flaky structure, and its BET specific surface area is 25m 2 / g to 50m 2 / g, preferably 30m 2 / g to 50m 2 / g, more preferably 35m 2 / g to 45m 2 / g.

[0011] According to one embodiment of the present application, the molecular sieve constituting the molecular sieve / carbon nitride composite material of the present application is ZSM-5.

[0012] Another technical problem to be solved by the present invention is to provide a method for preparing a molecular sieve / carbon nitride composite material, which comprises the following steps:

[0013] (1) mixing a silicon source solution and an aluminum source solution to obtain a silicon-aluminum source mixed solution;

[0014] (2) adding carbon nitride solid to the silicon-aluminum source mixed solution to obtain a crystallization precursor solution;

[0015] (3) filling the crystallization precursor solution into the crystallization kettle for crystallization treatment;

[0016] (4) subjecting the crystallized mixture to a post-treatment step to obtain a molecular sieve / carbon nitride composite material.

[0017] According to one embodiment of the present application, step (1) comprises

[0018] - Mix the template and water, then add the silicon source, and stir at 30-50°C for 1-24h to obtain a silicon source solution;

[0019] - Dissolve the alkali metal hydroxide in water, then add the aluminum source, and stir at room temperature for 1 to 24 hours to obtain an aluminum source solution;

[0020] -Mix the silicon source solution and the aluminum source solution, and stir at room temperature for 1 to 12 hours to obtain a silicon-aluminum source mixed solution.

[0021] According to one embodiment of the present application, the template is one or more selected from tetrapropylammonium bromide, tetrapropylammonium hydroxide, n-butylamine, and hexamethylenediamine; the silicon source is one or more selected from methyl orthosilicate, ethyl orthosilicate, water glass, and silica sol.

[0022] According to one embodiment of the present application, the aluminum source is one or more selected from sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum isopropoxide, and aluminum sol; the alkali metal hydroxide is selected from sodium hydroxide, potassium hydroxide, or a combination thereof.

[0023] According to one embodiment of the present application, in step (1), the dosage ratio of each material is such that, based on the molar ratio, R / SiO2 in the final silicon-aluminum source mixed solution is 0.05-0.5, wherein R is a template; preferably 0.193-0.335.

[0024] According to one embodiment of the present application, in step (1), the dosage ratio of each material is such that, based on the molar ratio, in the final silicon-aluminum source mixed solution, SiO2 / Al2O3=10-400, preferably 24-26.3.

[0025] According to one embodiment of the present application, in step (1), the dosage ratio of each material is such that, based on the molar ratio, in the final silicon-aluminum source mixed solution, H2O / SiO2=10-85, preferably 55.6-77.7.

[0026] According to one embodiment of the present application, in step (1), the dosage ratio of each material is such that, based on the molar ratio, in the final silicon-aluminum source mixed solution, Na2O / SiO2=0.03-1.6; preferably 0.097-0.423.

[0027] According to one embodiment of the present application, in step (1), the dosage ratio of each material is such that, based on the molar ratio, in the final silicon-aluminum source mixed solution, OH - / SiO2=0.01~1.6; preferably 0.387-0.762.

[0028] According to one embodiment of the present application, the silicon-aluminum source mixed solution having the above-mentioned dosage ratio is used in step (2), and in step (2), the mass of carbon nitride solid added to each mL of the silicon-aluminum source mixed solution is 0.02 to 0.2 g.

[0029] According to one embodiment of the present application, the post-treatment step includes solid-liquid separation, washing, drying and calcining the mixture after the crystallization treatment.

[0030] According to one embodiment of the present application, the carbon nitride solid in step (2) is a carbon nitride with a high specific surface area; when observed under TEM, the carbon nitride with a high specific surface area is in a flaky structure, and its BET specific surface area is 25 m 2 / g to 50m 2 / g, preferably 30m 2 / g to 50m 2 / g, more preferably 35m2 / g to 45m 2 / g.

[0031] According to one embodiment of the present application, high specific surface area carbon nitride is prepared as follows:

[0032] Melamine is heated to 530-580°C at a heating rate of 2-10°C / min, maintained for 3-5 hours, and cooled to room temperature to obtain low specific surface area carbon nitride; the specific surface area of ​​the low specific surface area carbon nitride is 5 to 15 m 2 / g;

[0033] The low specific surface area carbon nitride is heated to 480-520° C. at a heating rate of 2-10° C. / min, maintained for 1-3 hours, and cooled to room temperature to obtain a high specific surface area carbon nitride.

[0034] According to one embodiment of the present application, in step (3), crystallization is performed at 160 to 180° C. in a dynamic crystallization manner for 12 to 60 hours.

[0035] According to one embodiment of the present application, the calcination is performed at a temperature of 500-600° C. for 4-6 hours to remove the organic template.

[0036] The present application also relates to the use of the molecular sieve / carbon nitride composite material described herein for photocatalytic reduction of carbon dioxide to CO.

[0037] By adopting the above technical solution, the present application has the following beneficial effects:

[0038] (1) In the composite material of the present application, the ZSM-5 molecular sieve and the carbon nitride material react by in-situ synthesis, so that in the obtained composite material, the molecular sieve and the carbon nitride are tightly combined, and the free carbon nitride is relatively small; and both the molecular sieve and the carbon nitride can be fully exposed;

[0039] (2) The molecular sieve / carbon nitride composite material of the present application has a high specific surface area and can fully contact with the reactant molecules;

[0040] (3) The molecular sieve / carbon nitride composite material of the present application has a strong adsorption capacity for photocatalytic reactant molecules, which is beneficial to improving the efficiency of the photocatalytic reaction;

[0041] (4) The raw materials in this application are cheap and easily available, and the preparation method is simple and direct, which is suitable for mass production. At the same time, the silicon-aluminum ratio and type of the molecular sieve in the composite material can be flexibly controlled, which is expected to be extended to the preparation of various catalytic materials and has high research and commercial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1is a SEM image of the composite material obtained according to Example 1 of the present application;

[0043] Figure 2 Carbon dioxide adsorption curves of various materials measured for this application. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the accompanying drawings and preferred embodiments. It should be understood that these descriptions are only for illustrative purposes and do not limit the scope of the present invention in any way.

[0045] It is known in the art that carbon nitride is a material with a relatively large molecular size, and its structure is shown below:

[0046]

[0047] The molecular sieve / carbon nitride composite material of the present application comprises a molecular sieve structure combined with carbon nitride; wherein the relative crystallinity of the molecular sieve / carbon nitride composite material is 25 to 70%, preferably 30-60%.

[0048] The composite material of the present application comprises a molecular sieve structure combined with carbon nitride; wherein based on the total weight of the composite material, the molecular sieve / carbon nitride composite material comprises 25 to 70 weight % of the molecular sieve combined with carbon nitride, preferably 30-60 weight %.

[0049] As used herein, the term "molecular sieve structure combined with carbon nitride" refers to a molecular sieve structure that reacts with carbon nitride through in-situ synthesis. Because the two interact with each other through a chemical reaction, the two are relatively tightly combined, resulting in relatively less free carbon nitride and free molecular sieve in the composite material.

[0050] According to one embodiment of the present application, in the molecular sieve / carbon nitride composite material, the carbon nitride is a high specific surface area carbon nitride; under TEM observation, the high specific surface area carbon nitride is a flaky structure, and its BET specific surface area is 25m 2 / g to 50m 2 / g, preferably 30m 2 / g to 50m 2 / g, more preferably 35m 2 / g to 45m 2 / g.

[0051] According to one embodiment of the present application, the molecular sieve constituting the molecular sieve / carbon nitride composite material of the present application is ZSM-5.

[0052] According to one embodiment of the present application, the molecular sieves constituting the molecular sieve / carbon nitride composite material of the present application include multiple types of molecular sieves, such as Na-type ZSM-5 molecular sieve, H-type ZSM-5 molecular sieve, Na-type Y molecular sieve, H-type Y molecular sieve, Na-type β molecular sieve, and Na-type β molecular sieve.

[0053] In the composite material of the present application, the molecular sieve reacts with the flaky carbon nitride in an in-situ synthesis manner through a chemical synthesis step, so that the molecular sieve and the carbon nitride in the composite material are tightly combined and both are fully exposed.

[0054] As described herein, the term "fully exposed" means that the molecular sieve structure is fully extended, so that its porous structure can be used to enhance the adsorption and capture of reactant molecules; on the other hand, the sheet-like carbon nitride structure itself is also fully extended, which increases the number of catalytic active sites and enhances the catalytic activity; as shown in the attached Figure 1 As shown, the two are tightly bound and can be fully exposed to the reactant molecules, so they can have stronger adsorption capacity and better catalytic performance in the photocatalytic reaction.

[0055] In addition, due to the close combination of molecular sieve and carbon nitride, the composite material of the present application also has a higher specific surface area, for example, the BET specific surface area is 100-200m 2 / g, preferably 110-190m 2 In another embodiment, the composite material of the present application also has a flexibly adjustable silicon-to-aluminum ratio, for example, 10-400, preferably 30-300.

[0056] Another object of the present application is to provide a method for preparing the molecular sieve / carbon nitride composite material described in the present application, wherein the method comprises the following steps:

[0057] (1) preparing a silicon-aluminum source mixed solution, comprising:

[0058] - Mix the template and water, then add the silicon source and stir to obtain a silicon source solution;

[0059] - dissolving an alkali metal hydroxide in water, then adding an aluminum source and stirring to obtain an aluminum source solution;

[0060] - mixing the silicon source solution and the aluminum source solution to obtain a silicon-aluminum source mixed solution;

[0061] (2) adding carbon nitride solid to the silicon-aluminum source mixed solution to obtain a crystallization precursor solution;

[0062] (3) subjecting the crystallization precursor solution to crystallization treatment;

[0063] (4) Post-treatment: After the crystallization treatment is completed, the mixture after the crystallization treatment is subjected to solid-liquid separation, and is filtered, washed, dried, and calcined in sequence to obtain a molecular sieve / carbon nitride composite material.

[0064] The water used in the above steps can be deionized water, distilled water, etc.

[0065] As described herein, the term "crystallization treatment" in step (3) refers to a process performed at 160-180°C in a dynamic crystallization manner for 12-60 hours. In one embodiment, the crystallization treatment may be performed in a crystallization reactor.

[0066] According to one embodiment of the present application, the carbon nitride solid in step (2) is a high specific surface area carbon nitride; under TEM observation, the high specific surface area carbon nitride has a flaky structure and a BET specific surface area of ​​25 m 2 / g to 50m 2 / g, preferably 30m 2 / g to 50m 2 / g, more preferably 35m 2 / g to 45m 2 / g.

[0067] According to one embodiment of the present application, high specific surface area carbon nitride is prepared as follows:

[0068] Melamine, preferably powder, is heated to 530-580°C at a heating rate of 2-10°C / min, maintained for 3-5 hours, and cooled to room temperature to obtain low specific surface area carbon nitride; the specific surface area of ​​the low specific surface area carbon nitride is 5 to 15 m 2 / g;

[0069] The low specific surface area carbon nitride is heated to 480-520° C. at a heating rate of 2-10° C. / min, maintained for 1-3 hours, and cooled to room temperature to obtain a high specific surface area carbon nitride.

[0070] As used herein, in the context of this application, "room temperature" refers to a temperature of about 20-35°C.

[0071] According to one embodiment of the present application, when preparing low specific surface area carbon nitride, the heating process is carried out in an air-tight manner. In another embodiment, the heating process can be carried out by placing the melamine powder in a container, such as a crucible, and then placing the crucible in a muffle furnace. For example, the heating process can be carried out as follows: the melamine powder is placed in a crucible, covered, placed in a muffle furnace, heated to 530-580°C at a heating rate of 2-10°C / min, maintained for 3-5 hours, and cooled to room temperature to obtain low specific surface area carbon nitride, which is a yellow powder.

[0072] According to another embodiment of the present application, when preparing high specific surface area carbon nitride, the heating of low specific surface area carbon nitride is carried out in contact with air. In one embodiment, the heating process can be carried out by placing the low specific surface area carbon nitride in a container, such as a crucible, and then placing the crucible in a muffle furnace. For example, the heating process can be carried out as follows: the low specific surface area carbon nitride is placed in a crucible without a cover, placed in a muffle furnace, heated to 480-520°C at a heating rate of 2-10°C / min, maintained for 1-3 hours, and cooled to room temperature to obtain a high specific surface area carbon nitride, which is a light yellow powder.

[0073] The method of the present application includes a chemical synthesis step, wherein preferably high specific surface area carbon nitride is added to a silicon-aluminum source mixed solution to obtain a crystallization precursor solution; then the crystallization precursor solution is subjected to a crystallization treatment. Finally, after a post-treatment step, the molecular sieve / carbon nitride composite material of the present application is obtained.

[0074] In the context of this application, the weight percentage of the molecular sieve structure bonded to the carbon nitride is calculated as follows

[0075] -Measure the XRD spectrum of commercial molecular sieve ZSM-5, and then measure the characteristic peak area between 22.5 and 25°, which is recorded as S1; at the same time, the relative crystallinity of the molecular sieve is defined as 100%;

[0076] - measuring the XRD spectrum of the composite material according to the present application, and then measuring the characteristic peak area at a 2θ angle between 22.5 and 25.0° in the XRD spectrum of the composite material, recorded as S2;

[0077] - Calculate S2 / S1*100%, which is the relative crystallinity of the composite material, which corresponds to the weight percentage of the molecular sieve structure combined with the carbon nitride in the composite material.

[0078] Without being limited to any theory, the inventors of the present application believe that the chemical synthesis step of the present application brings unexpected technical effects to the present application. This is because, as known in the art, carbon nitride is an alkaline substance with a large molecular size. Through the chemical synthesis step, more particularly, by controlling the temperature, heating time, crystallization treatment process and material ratio of each material used in the process, the method of the present application can effectively peel off the layered carbon nitride, and can improve the dispersion uniformity of the carbon nitride / molecular sieve. In addition, due to the alkalinity of the carbon nitride molecule, it can react with the acidic sites on the outer surface of the molecular sieve. Under the process conditions of the method of the present application, the molecular sieve is tightly combined with the carbon nitride, does not contain or substantially does not contain free carbon nitride substances, and both the molecular sieve and the carbon nitride can be fully exposed. As described above, "fully exposed" enables the composite material of the present application to have more reaction sites, stronger adsorption capacity and therefore, better catalytic performance in the photocatalytic reaction.

[0079] The molecular sieve / carbon nitride composite material of the present application can be used in the field of photocatalysis, for example, can be used to convert CO2 into CO through photocatalysis.

[0080] It is known in the art that under certain light conditions, semiconductor materials such as carbon nitride can be excited to produce electrons and holes, which remain in their valence band and conduction band, respectively. The excited electrons in the conduction band have strong reducing ability and can reduce CO2 to products such as CO.

[0081] When the molecular sieve / carbon nitride composite material described in the present application is used for the photocatalytic reaction of converting CO2 into CO, the molecular sieve can utilize its porous structure to achieve the adsorption and / or capture of reactant molecules (i.e., CO2); on the other hand, the carbon nitride acts as a catalyst to reduce CO2 to products such as CO.

[0082] By using the molecular sieve / carbon nitride composite material according to the present application, the present application can obtain a satisfactory CO generation rate, for example, 0.05 to 1 μmol·h -1 ·g -1 , preferably 0.14 to 0.82 μmol·h -1 ·g -1 The CO production rate.

[0083] As described above, in the composite material of the present application, both the carbon nitride molecules and the molecular sieve structure can be fully exposed to the reactant molecules, so that the molecular sieve of the present application has a significantly larger specific surface area, and therefore, the composite material of the present application can have significantly better adsorption performance. Figure 2As shown, under the same conditions, the adsorption capacity of the composite material according to the present application is significantly better than that of a single molecular sieve, a single carbon nitride, and a simple mixed molecular sieve / carbon nitride. More specifically, under the same conditions, the adsorption capacity of the composite material according to the present application is significantly higher than that of the above-mentioned comparative example, even 2 times higher, which is an unexpected technical effect.

[0084] More specifically, since both carbon nitride and molecular sieve can be fully exposed to reactant molecules in the composite material of the present application, the composite material of the present application has significantly more reaction sites, thus obtaining significantly better catalytic performance. For example, in the CO2 reduction reaction described in the present application, the composite material of the present application can obtain a significantly higher CO generation rate, for example, 0.05 to 1 μmol·h -1 ·g -1 , preferably 0.14 to 0.82 μmol·h -1 ·g -1 The CO production rate.

[0085] Example

[0086] The present application will be further described below in conjunction with specific examples, but it should be understood that the specific examples given are only for illustration and do not limit the present invention in any way. In the following examples, room temperature refers to a temperature of about 25°C.

[0087] The specific surface area and mesoporous specific surface area mentioned in this article are measured by BET method. The method of measuring pore size distribution by nitrogen adsorption capacity method refers to the analysis method of RIPP151-90 (Petrochemical Analysis Method, RIPP Test Method, Science Press, published in 1990).

[0088] The relative crystallinity is measured as follows:

[0089] Referring to ASTM D3906-03 standard, commercial ZSM-5 molecular sieve is used as the standard (Tianjin Nanhua Catalyst Co., Ltd., Na-type ZSM-5 molecular sieve of Nankai University Catalyst Factory, silicon-aluminum ratio is 50); the XRD spectrum of commercial molecular sieve ZSM-5 is measured, and then the characteristic peak area between 22.5 and 25° of the 2θ angle is measured, which is recorded as S1; at the same time, the relative crystallinity of the molecular sieve is defined as 100%;

[0090] Measure the XRD spectrum of the composite material according to the present application, and then measure the characteristic peak area at a 2θ angle between 22.5 and 25.0° in the XRD spectrum of the composite material, which is recorded as S2;

[0091] Calculate S2 / S1*100%, which is the relative crystallinity of the composite material. The relative crystallinity corresponds to the weight percentage of the molecular sieve structure combined with carbon nitride in the composite material.

[0092] Test instrument: D5005 X-ray diffractometer from Siemens, Germany. Test conditions: Cu target, Kα radiation, solid detector, tube voltage 40 kV, tube current 40 mA, step scan, step width 0.02°, pre-set time 2 s, scan range 5°~70°.

[0093] The silicon-aluminum ratio is measured as follows:

[0094] The silicon-aluminum ratio was quantitatively characterized by X-ray fluorescence method.

[0095] Test instrument: 3271E X-ray fluorescence spectrometer produced by Rigaku Corporation of Japan.

[0096] Experimental conditions: powder samples were pressed into tablets, rhodium target, excitation voltage 50 kV, excitation current 50 mA, scintillation counter and proportional counter were used to detect the intensity of the spectral lines of each element, and the external standard method was used to perform quantitative and semi-quantitative analysis of the element content.

[0097] Example 1

[0098] (1) Preparation of low specific surface area carbon nitride: 5 g of melamine powder was placed in a crucible (covered), placed in a muffle furnace, heated to 550°C at a heating rate of 2.5°C / min, and maintained for 4 hours. After cooling to room temperature, yellow powder was obtained, i.e., low specific surface area carbon nitride. The BET specific surface area of ​​the carbon nitride was tested to be 9.7 m 2 / g.

[0099] (2) Preparation of high specific surface area carbon nitride: The obtained low specific surface area carbon nitride powder was placed in a crucible (without a cover), placed in a muffle furnace, heated to 500°C at a heating rate of 5°C / min, and maintained for 2 hours. After cooling to room temperature, a light yellow powder was obtained, i.e., high specific surface area carbon nitride. Under TEM observation, the carbon nitride had a flaky structure; its BET specific surface area was tested to be 30.5 m 2 / g.

[0100] (3) Prepare a crystallization precursor solution: add 53.7 grams of tetrapropylammonium hydroxide solution (25 wt%) to 148 grams of deionized water, stir at room temperature for 15 minutes, then add 42.7 grams of tetraethyl orthosilicate (silicon source), stir in a 40°C water bath for 1.5 hours to obtain a silicon source solution; add 1.8 grams of sodium hydroxide particles to 20 grams of deionized water, add 6.3 grams of aluminum nitrate after complete dissolution, stir at room temperature for 1.5 hours to obtain an aluminum source solution. Mix the above silicon source solution and aluminum source solution, stir at room temperature for 4 hours to obtain a silicon-aluminum source mixed solution. Add 2 g of the flaky carbon nitride obtained in step (2) to 40 mL of the silicon-aluminum source mixed solution to obtain a crystallization precursor solution.

[0101] (4) Crystallization: The crystallization precursor solution was loaded into a crystallization kettle and dynamically crystallized at 170°C for 48 hours.

[0102] (5) Post-treatment: After the crystallization is completed, the crystallized mixture is subjected to solid-liquid separation, and is filtered, washed, and dried in sequence. The dried crystallized product is calcined at 550°C for 4 hours to remove the organic template therein, and a molecular sieve / graphite carbon nitride composite material is obtained, and its BET specific surface area and relative crystallinity data are shown in Table 2.

[0103] Example 2

[0104] (1) Preparation of low specific surface area carbon nitride: 5 g of melamine powder was placed in a crucible (covered), placed in a muffle furnace, heated to 560°C at a heating rate of 3°C / min, and maintained for 3.5 hours. After cooling to room temperature, yellow powder was obtained, i.e., low specific surface area carbon nitride. The BET specific surface area of ​​the carbon nitride was tested to be 10.4 m 2 / g

[0105] (2) Preparation of high specific surface area carbon nitride: The obtained low specific surface area carbon nitride powder was placed in a crucible (without a cover), placed in a muffle furnace, heated to 500°C at a heating rate of 8°C / min, and maintained for 2.5 hours. After cooling to room temperature, a light yellow powder was obtained, i.e., high specific surface area carbon nitride. Under TEM observation, the carbon nitride had a flaky structure; its BET specific surface area was tested to be 31.7 m 2 / g.

[0106] (3) Prepare a crystallization precursor solution: add 20.7 grams of tetrapropylammonium bromide solution (25 wt%) to 292 grams of deionized water, stir at room temperature for 15 minutes, then add 65.8 grams of methyl orthosilicate (silicon source), stir in a 35°C water bath for 4 hours to obtain a silicon source solution; add 9.64 grams of sodium hydroxide particles to 12 grams of deionized water, add 2.87 grams of sodium aluminate after complete dissolution, stir at room temperature for 2 hours to obtain an aluminum source solution. Mix the above silicon source solution and aluminum source solution, stir at room temperature for 4 hours to obtain a silicon-aluminum source mixed solution. Add 5 grams of the flaky carbon nitride obtained in step (2) to 40 mL of the silicon-aluminum source mixed solution to obtain a crystallization precursor solution.

[0107] (4) Crystallization: The crystallization precursor solution was loaded into a crystallization kettle and dynamically crystallized at 180°C for 30 h.

[0108] (5) Post-treatment: After the crystallization is completed, the crystallized mixture is subjected to solid-liquid separation, and then filtered, washed, and dried in sequence. The dried crystallized product is calcined at 500°C for 6 hours to remove the organic template therein, and a molecular sieve / graphite carbon nitride composite material is obtained, and its BET specific surface area and relative crystallinity data are shown in Table 2.

[0109] Example 3

[0110] (1) Preparation of low specific surface area carbon nitride: 5 g of melamine powder was placed in a crucible (covered), placed in a muffle furnace, heated to 560°C at a heating rate of 4°C / min, and maintained for 4 hours. After cooling to room temperature, a yellow powder, i.e., low specific surface area carbon nitride, was obtained. Under TEM observation, the BET specific surface area of ​​the carbon nitride was 10.8 m 2 / g.

[0111] (2) Preparation of high specific surface area carbon nitride: The obtained low specific surface area carbon nitride powder was placed in a crucible (without a cover), placed in a muffle furnace, heated to 490°C at a heating rate of 5°C / min, and maintained for 3 hours. After cooling to room temperature, a light yellow powder was obtained, i.e., high specific surface area carbon nitride. Under TEM observation, the carbon nitride had a flaky structure; its BET specific surface area was tested to be 33.6 m 2 / g.

[0112] (3) Prepare a crystallization precursor solution: add 41.6 grams of tetrapropylammonium hydroxide solution (25 wt%) to 332 grams of deionized water, stir at room temperature for 20 minutes, then add 57.4 grams of tetraethyl orthosilicate (silicon source), stir in a 45°C water bath for 1 hour to obtain a silicon source solution; add 2.14 grams of sodium hydroxide particles to 16 grams of deionized water, add 4.2 grams of aluminum isopropoxide after complete dissolution, stir at room temperature for 1.5 hours to obtain an aluminum source solution. Mix the above silicon source solution and aluminum source solution, stir at room temperature for 4 hours to obtain a silicon-aluminum source mixed solution. Add 7 grams of flaky carbon nitride obtained in step (2) to 40 mL of the silicon-aluminum source mixed solution to obtain a crystallization precursor solution.

[0113] (4) Crystallization: The crystallization precursor solution was loaded into a crystallization kettle and dynamically crystallized at 160°C for 52 h.

[0114] (5) Post-treatment: After the crystallization is completed, the crystallized mixture is subjected to solid-liquid separation, and is filtered, washed, and dried in sequence. The dried crystallized product is calcined at 550°C for 4 hours to remove the organic template therein, and a molecular sieve / graphite carbon nitride composite material is obtained, and its BET specific surface area and relative crystallinity data are shown in Table 2.

[0115] Comparative Example 4

[0116] The high specific surface area carbon nitride prepared in Example 1 was directly and simply mixed with commercial ZSM-5 molecular sieve (Nankai Catalyst Company, NKF-5, silicon-aluminum molecular ratio 25) in a mass ratio of 42:58 to obtain a molecular sieve-carbon nitride composite material with a molecular sieve content (58%).

[0117] Table 1. Molar ratios of various substances in the precursor solution in the examples according to the present application

[0118] The molar ratio in the precursor solution Example 1 Example 2 Example 3 <![CDATA[SiO2 / Al2O3]]> 24.0 24 26.3 <![CDATA[R / SiO2]]> 0.335 0.251 0.193 <![CDATA[H2O / SiO2]]> 56.1 55.6 77.7 <![CDATA[Na2O / SiO2]]> 0.110 0.423 0.097 <![CDATA[OH - / SiO2]]> 0.554 0.762 0.387

[0119] It can be seen from Table 1 above that by changing the feed dosage, the molar ratio of each substance in the precursor solution can be adjusted, and the in-situ synthesis of the molecular sieve can be completed in different crystallization systems, indicating that the method of the present invention is applicable to a variety of crystallization conditions;

[0120] Table 2. Measurement results of the obtained composite materials

[0121]

[0122]

[0123] Note: S micro Refers to the micropore specific surface area measured by the BET method; S meso Refers to the mesopore specific surface area measured by the BET method; S BET Refers to the total specific surface area measured by the BET method.

[0124] From the scanning electron microscope image ( Figure 1 ) It can be seen that in the composite material according to the present application, the molecular sieve structure and the flaky carbon nitride are tightly combined and both can be fully exposed, which makes the molecular sieve have a relatively larger specific surface area on the one hand, and can utilize its pore structure to adsorb / capture more substrate molecules; on the other hand, the full exposure of the flaky carbon nitride structure significantly increases the catalytic reaction sites of the composite material, and the synergistic effect of the two significantly improves the catalytic activity of the resulting composite material.

[0125] Taking carbon dioxide as the model molecule of photocatalytic reactant, the adsorption of carbon dioxide molecules by various materials was tested. The test method is as follows:

[0126] The carbon dioxide adsorption capacity was tested using a Micromeritics TriStar II 3020 gas adsorption instrument. The test conditions were as follows: adsorption gas: CO2; degassing temperature: 200°C; degassing time: 8 hours; test temperature: 25°C.

[0127] Results Figure 2 .Depend on Figure 2 It can be seen that the molecular sieve / carbon nitride composite material according to the present application has a strong adsorption effect on carbon dioxide molecules. Specifically: when P / P0=1, Comparative Example 1 is carbon nitride itself, and the CO2 adsorption amount is 0.95mmol / g; Comparative Example 2 is molecular sieve itself, and the CO2 adsorption amount is 1.3mmol / g; Comparative Example 3 is a simple mixture of the two (carbon nitride: molecular sieve mass ratio = 1:1), and the CO2 adsorption amount is 1.1mmol / g ( Figure 2Not shown, this is an experimental result); in comparison, the adsorption capacity of the composite material according to Example 1 of the present application is 2.3 mmol / g, which is about 2 times the maximum adsorption capacity of all comparative examples, indicating that the composite material according to the present application has a significantly higher CO2 adsorption capacity.

[0128] Photocatalytic reaction evaluation

[0129] The molecular sieve / carbon nitride composite material obtained in the above embodiment was evaluated in the PerfectLight, Labsolar-6A photocatalytic system using photocatalytic carbon dioxide reduction as a model reaction. The test conditions are as follows. Light source type: PerfectLight, PLS-SXE300, AM1.5G (simulated sunlight); light source power: 300W xenon lamp; distance between light source and reactor: 4cm; cooling method: cooling circulating water; reaction temperature: 25°C; gas chromatograph model: Kechuang GC2002; carrier gas type: Ar; injector temperature: 160°C; catalyst sample amount: 100mg; column temperature: 60°C; detector type: TCD detector; TCD channel temperature: 110°C; current: 60mA. The amount of CO generated by the reaction system at different times was detected by gas chromatography, and the CO generation rate was calculated by CO generation / reaction time.

[0130] The molecular sieve / carbon nitride composite material obtained in the above example was tested for carbon dioxide adsorption using a Micromeritics TriStar II 3020 gas adsorption instrument. The test conditions were as follows: adsorption gas: CO2; degassing temperature: 200°C; degassing time: 8 hours; test temperature: 25°C.

[0131] The results of the main reduction product (CO) generation rate are listed in Table 3. At room temperature, the CO generation rate is 0.14-0.82 μmol·h -1 ·g -1 .

[0132] Table 3 CO generation rate of each example

[0133]

[0134] It can be seen from Table 3 that the embodiments according to the present application can obtain satisfactory CO yields, which are significantly higher than that of Comparative Example 4 using simple mixing. In addition, Example 1 and Comparative Example 4 have the same molecular sieve content (see Table 2), but as shown in Table 3, the CO production rate of Example 1 according to the present application is significantly greater than that of Comparative Example 4, which is about 56% higher than that of Comparative Example 4, which is an unexpected technical effect, indicating that in the composite material described in the present application, the close combination of molecular sieve and carbon nitride produces a significant synergistic effect on the catalytic performance.

[0135] It can also be seen that the CO generation rate of Example 3 is the highest. This is because the composite material of Example 3 has a relatively high carbon nitride content and the molecular sieve and carbon nitride have a relatively better synergistic effect.

Claims

1. A molecular sieve / carbon nitride composite material, wherein the molecular sieve / carbon nitride composite material comprises 25 to 70 weight percent of molecular sieve combined with carbon nitride based on the total weight of the composite material, and the molecular sieve / carbon nitride composite material has a BET specific surface area of ​​100 m 2 / g to 200m 2 / g, silicon-aluminum ratio is 10-400; The molecular sieve / carbon nitride composite material is prepared by a method comprising the following steps: (1) mixing a silicon source solution and an aluminum source solution to obtain a silicon-aluminum source mixed solution; (2) adding carbon nitride solid to the silicon-aluminum source mixed solution to obtain a crystallization precursor solution; (3) subjecting the crystallization precursor solution to crystallization treatment; (4) subjecting the crystallized mixture to a post-treatment step to obtain a molecular sieve / carbon nitride composite material; The carbon nitride solid in step (2) is a carbon nitride with a high specific surface area; under TEM observation, the carbon nitride with a high specific surface area is a flaky structure, and its BET specific surface area is 25 m 2 / g to 50m 2 / g.

2. The molecular sieve / carbon nitride composite material according to claim 1, wherein the BET specific surface area of ​​the carbon nitride is 30 m 2 / g to 50m 2 / g. The molecular sieve / carbon nitride composite material according to claim 1 , wherein the molecular sieve is ZSM-5.

4. The molecular sieve / carbon nitride composite material according to claim 1, wherein the BET specific surface area of ​​the carbon nitride is 35 m 2 / g to 45m 2 / g.

5. A method for preparing the molecular sieve / carbon nitride composite material according to any one of claims 1 to 4, wherein the method comprises the following steps: (1) mixing a silicon source solution and an aluminum source solution to obtain a silicon-aluminum source mixed solution; (2) adding carbon nitride solid to the silicon-aluminum source mixed solution to obtain a crystallization precursor solution; (3) subjecting the crystallization precursor solution to crystallization treatment; (4) subjecting the crystallized mixture to a post-treatment step to obtain a molecular sieve / carbon nitride composite material; The carbon nitride solid in step (2) is a carbon nitride with a high specific surface area; under TEM observation, the carbon nitride with a high specific surface area is a flaky structure, and its BET specific surface area is 25 m 2 / g to 50m 2 / g.

6. The method according to claim 5, wherein the silicon source solution is obtained by mixing the template and water, then adding the silicon source and stirring.

7. The method according to claim 5, wherein the aluminum source solution is obtained by dissolving an alkali metal hydroxide in water, followed by adding an aluminum source and stirring.

8. The method according to claim 5, wherein the post-treatment step comprises subjecting the mixture after the crystallization treatment to solid-liquid separation, washing, drying and calcining.

9. The method according to claim 6, wherein the template is one or more selected from tetrapropylammonium bromide, tetrapropylammonium hydroxide, n-butylamine, and hexamethylenediamine; the silicon source is one or more selected from methyl orthosilicate, ethyl orthosilicate, water glass, and silica sol; and the aluminum source is one or more selected from sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum isopropoxide, and aluminum sol.

10. The method according to claim 5, wherein in step (1), the dosage ratio of each material is such that, based on the molar ratio, in the final silicon-aluminum source mixed solution, R / SiO2=0.05-0.5, wherein R is a template; SiO2 / Al2O3=10-400; H2O / SiO2=10-85; Na2O / SiO2=0.03-1.6; OH - / SiO2=0.01~1.

6.

11. The method according to claim 5, wherein the BET specific surface area of ​​the carbon nitride is 30 m 2 / g to 50m 2 / g.

12. The method according to claim 5, wherein the BET specific surface area of ​​the carbon nitride is 35 m 2 / g to 45m 2 / g.

13. The method according to claim 11, wherein the high specific surface area carbon nitride is prepared as follows: Melamine is heated to 530-580°C at a heating rate of 2-10°C / min, maintained for 3-5 hours, and cooled to room temperature to obtain low specific surface area carbon nitride; the specific surface area of ​​the low specific surface area carbon nitride is 5 to 15 m 2 / g; The low specific surface area carbon nitride is heated to 480-520° C. at a heating rate of 2-10° C. / min, maintained for 1-3 hours, and cooled to room temperature to obtain a high specific surface area carbon nitride.

14. The method according to claim 10, wherein the silicon-aluminum source mixed solution having the above dosage ratio is used in the step (2), and in the step (2), the mass of carbon nitride solid added to each mL of the silicon-aluminum source mixed solution is 0.02-0.2 g.

15. The method according to claim 5, wherein in step (3), the crystallization treatment is carried out at a temperature of 160 to 180°C for 12 to 60 hours in a dynamic crystallization manner.

16. The method according to claim 8, wherein the calcination is carried out at a temperature of 500-600°C for 4-6 hours.

17. The method of claim 7, wherein the alkali metal hydroxide is selected from sodium hydroxide, potassium hydroxide, or a combination thereof.

18. Use of the molecular sieve / carbon nitride composite material according to claim 1 for reducing carbon dioxide to CO through photocatalysis.

Citation Information

Patent Citations

  • Preparation method for zeolite-immobilized photocatalyst

    CN106362787A

  • Two-dimensional carbon nitride photocatalyst containing D-A structure as well as preparation method and application thereof

    CN112371145A

  • ZSM-5 molecular sieve as well as preparation method and application thereof

    CN112794338A